Chronology of post-embryonic development in Siriella armata (M.Edw.) ( Crustacea: Mysidacea) reared in the laboratory: growth and sexual differentiation - CUZIN-ROUDY, J., BERREUR-BONNENFANT, J.; FRIED-MONTAUFIER, M.C. (International Journal of invertebrate Reproduction, 4: 193-208., 1981)
GOBSYS
NeMys doc_id: 3769